COMMUNITY PARTICIPATION IN WASTE MANAGEMENT IN BATUNUNGGAL INDAH RESIDENTIAL AREA, BANDUNG, INDONESIA - Anni Rochaeni; Ria Ismaria; Dede Sulaeman; Bryan Yogi Nurfryatna (Journal of Community Based Environmental Engineering and Management, 2021)
Batununggal Indah housing still faces obstacles in waste management due to the low awareness of the community to separate and sort waste. Therefore, this area is the target of implementing waste management assistance carried out by the Bandung City Environment and Sanitation Service (DLHK) in collaboration with the City Government of Kawasaki, Japan. This study aims to evaluate the implementation of the waste management program in Permai and Jelita Clusters by identifying activities, changing community behavior and calculating changes in the amount of waste that is disposed of at the final disposal site. The evaluation results show that the main activity that has been carried out is a social approach in the form of workshops and counseling. Measurement of waste generation shows a decrease in the weight of generated waste that is disposed of at the final disposal site, indicating that waste separation has been practiced. This decrease is still insignificant because the community has not consistently carried out sorting behavior, so it needs sustainable encouragement.